(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to determine the social class described in Charlotte Bronte’s Jane Eyre and to understand the love relationship between people of different social Classes in Charlotte Bronte’s Jane Eyre. This study found that there are three Classes in the novel, namely the upper class, the middle class and the lower class. In novels, social class can be shown through the behavior, actions, and feelings of the characters who occupy different social classes. The second finding is about the love relationship between Jane Eyre and Mr. Rochester. Their love faces obstacles such as; a secret about Mr. Rochester’s first marriage and Mr. Rochester’s accident that caused his blindness.